Processing and Formation of Bioactive CLE40 Peptide Are Controlled by Posttranslational Proline Hydroxylation - Stührwohldt, Nils (Plant Physiol, 2020)
Small posttranslationally modified signaling peptides are proteolytically derived from larger precursor proteins and subject to several additional steps of modification, including Pro hydroxylation, Hyp glycosylation, and/or Tyr sulfation. The processing proteases and the relevance of posttranslational modifications for peptide biogenesis and activity are largely unknown. In this study these questions were addressed for the Clavata3/Endosperm Surrounding Region (CLE) peptide CLE40, a peptide regulator of stem cell differentiation in the Arabidopsis (Arabidopsis thaliana) root meristem. We identify three subtilases (SBT1.4, SBT1.7, and SBT4.13) that cleave the CLE40 precursor redundantly at two sites. C-terminal processing releases the mature peptide from its precursor and is thus required for signal biogenesis. SBT-mediated cleavage at a second site within the mature peptide attenuates the signal. The second cleavage is prevented by Pro hydroxylation, resulting in the formation of mature and bioactive CLE40 in planta. Our data reveal a role for posttranslational modification by Pro hydroxylation in the regulation of CLE40 formation and activity.